Wireless monitoring for assessment of concrete railway bridges – Experiences from field tests - Täljsten, Björn; Popescu, Cosmin; Nilforoush, Rasoul (Luleå tekniska universitet, Byggkonstruktion och brand, 2022)
This paper focus on assessment on a prestressed three span concrete box bridge by the use of a wireless monitoring system in combination with visual inspection. The bridge is located in the very north of Sweden, in Abisko. A visual inspection of the bridge carried out the 18th of August in 2016 several crack patterns were mapped on the inside of the box girder bridge located near supports in the spans on both sides of the bridge. The cause of the cracks are not completely clear. To reveal the reason for cracking a long term project has been initiated by Trafikverket. Here a new developed wireless system has been used. Investigating change in crack widths by the use of LVDTs and strain gauges. Also accelerations are monitored together with the temperatures. In addition also fibre optic systems and non-destructive tests were carried out (not reported here). The results/conclusions presented in the paper are preliminary and final results will be presented 2021. In2Track: Research into enhanced tracks, switches and structures